BMI and adipocytokine changes in COPD exacerbation and stable COPD - Cambay, Zafer; Ilhan, Nevin; Susam, Solmaz; Muz, Mehmet Hamdi (Natl Inst Science Communication-Niscair, 2021)
COPD is described by progressive airflow restriction and recurrent acute exacerbations, which is caused by inflammatory response occurring in lungs as a result of chronic inhalation of harmful particles and gases. The study was designed to determine the link of interleukin-6 (IL-6), adiponectin and visfatin with BMI and oxidant/antioxidant balance in Chronic Obstructive Pulmonary Disease (COPD), a systemic disease. The study comprised control (n=20), patients with COPD (n=37) from the Chest Diseases Clinic of Firat University Hospital. The serum MDA, IL-6, Visfatin and Adiponectin levels were evaluated by ELISA. Also, Pulmonary Function Tests were done. There was no significant difference between control and patients with COPD in terms of sex and age averages. On the contrary, BMI levels were statistically significantly lower in COPD group compared to the controls. MDA and adiponectin levels were higher, IL-6 and visfatin levels were lower in COPD groups contrary to controls. It was thought that the level changes of these parameters (MDA, IL-6, visfatin and adiponectin) may be an important factor in the development of COPD and in monitoring the treatment of COPD-related diseases.
Keywords: Adiponectin; Chronic obstructive pulmonary disease (COPD); Interleukin-6; Malondialdehyde (MDA); Visfatin